ANALISIS LINGKUNGAN KERJA, MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PTPN II SEI SEMAYANG - Nasution, Fat’hul Fahrozi; Pratama , Siswa; Robain, Wilchan (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The research analysis aims to analyze the work environment, work motivation and work discipline on the productivity of PTPN II Sei Semayang employees. The data analysis technique used is an associative research method with the help of the SPSS version 19 program. This research uses multiple linear regression analysis. The sample in this study was 64 respondents. Primary data collection uses a questionnaire. The results of the research show that testing for the work environment variable shows a tcount value of 4.246 > ttable of 2.00 with a significant value of 0.000 <0.05, so the hypothesis H1 is accepted and H0 is rejected, meaning that the work environment has a partially positive and significant effect on work productivity. PTPN II Sei Semayang employees. The test results for the work motivation variable show a tcount value of 2.286 > ttable of 2.00 with a significant value of 0.026 < 0.05, so hypothesis H2 is accepted and H0 is rejected, meaning that work motivation has a partially positive and significant effect on the work productivity of PTPN II employees Sei Semayang. The test results for the work discipline variable show a tcount value of 2.523> ttable of 2.00 with a significant value of 0.014<0.05, so hypothesis H3 is accepted and H0 is rejected, meaning that work discipline has a partially positive and significant effect on the work productivity of PTPN II employees Sei Semayang, Simultaneous test results with a calculated F value of 20.869 which is greater than 2.76 and a significant value of 0.000 is smaller than 0.05 so it can be concluded that hypothesis 4 is accepted and hypothesis 0 is rejected so it can be concluded that the work environment, work motivation and work discipline have a significant effect simultaneously on the work productivity of PTPN II Sei Semayang employees.